Impact Of Hypothyroidism On Infertility: A Cross Sectional Study In Tertiary Health Care Centre - Dr. G. Ravi Kumar, Dr.D.V.S. Priyadarshini, Dr.K.Kiranmayi, Dr. Tanuja Paipuru (International Journal of Advanced Science and Technology, 2020)
Background: Adequate levels of circulating thyroid hormones are of primary importance for normal reproductive function. Thyroid dysfunction has a great impact on fertility in women. Prevalence of hypothyroidism is 2–4% in women in the reproductive age group. Hypothyroidism can affect fertility due to anovulatory cycles, luteal phase defects, hyperprolactinemia, and sex hormone imbalance. Aims and Objectives: To study the prevalence of clinical/sub-clinical hypothyroidism in infertile women Materials and Methods: A total of 300 infertile women visiting the infertility clinic for the first time were investigated for thyroid stimulating hormone (TSH) and prolactin (PRL). Infertile women with hypothyroidism alone or with associated hyperprolactinemia were given treatment for hypothyroidism with thyroxine 25–150 μg. Results: Of 300 infertile women, 30% were hypothyroid (TSH > 4.2 μIU/ml). After treatment for hypothyroidism, 70% of infertile women conceived within 6 weeks to 1 year. Infertile women with both hypothyroidism and hyperprolactinemia also responded to treatment and their PRL levels returned to normal. Conclusion: Measurement of TSH and PRL should be done at early stage of infertility check up rather than straight away going for more costly tests or invasive procedures. Simple oral treatment for about 6 months to 1 year could be beneficial for the infertile women to conceive. Keywords: Infertility, Hypothyroidism, Prolactin, TSH,